WINGKO BABAT PRODUCT DEVELOPMENT STRATEGY FOR COMPETITIVE ADVANTAGE DURING THE COVID-19 PANDEMIC - Mohammad Yaskun; Danu Kusbandono; Wisnu Priambodo (JURNAL ILMIAH EDUNOMIKA, 2021)
Wingko is a special snack that comes from Babat, Lamongan. In its development wingko spread in various areas in Lamongan and surrounding areas. The wingko tripe industry in 2010 was able to produce up to 1.500 wingko each day, while in 2020 it decreased to 1.000 wingko/day. The competition that occurs makes production unstable, even decreased. Therefore, research is needed on the strategy of wingko Babat industrial development. This research aims to design a wingko Babat industrial development strategy to develop and open jobs for the surrounding residents and increase the original income of the Lamongan regency. This research was conducted in January-May 2021 on wingko Babat industry players using Fred R David's Strategy Formulation Framework method that combines External Factor Evaluation (EFE) and Internal Factor Evaluation (IFE) data, then conducted SWOT and Grand Strategy analysis. The results of this study show that several strategies must be carried out by the wingko Babat industry; maintaining product quality, product development, taking care of halal permits, marketing with online media, product diversification, improving business management systems, and establishing cooperation with local governments. Therefore, wingko Babat industry players are expected to be able to implement some of these strategies to be able to compete, especially during the covid-19 pandemic.